PENYUSUNAN LAPORAN KEUANGAN PADA PIZZA ZAZA DAN FERA KUE MENGGUNAKAN APLIKASI UKM - Berlian Afriansyah (Jurnal Ilmiah Raflesia Akuntansi, 2021)
Abstrack-This study aims to determine financial reporting on Pizza Zaza and Fera Kue using the UKM application. The object of this study is the financial statements of SMEs on Pizza Zaza and Fera Kue which were recorded in 2019. Transactions that were recorded using the UKM application version 2018.The results of this study are generally output from this SME application which consists of journals, ledgers, trial balances, profit and loss, and balance sheet reports for one year. Based on the results of the SME application output obtained financial statements during 2019 including a trial balance of IDR 297,537,100.00, profit and loss of IDR 31,932,500.00 and a balance sheet report of IDR 262,883,100.00.